Analysis of maritime transportation research capability: authors, affiliations, and nationalities - Lin Lin; Tingsong Wang; Ping Zhang; Rui Roy Han; Guangfu Liu; Yanhui Li (Taylor & Francis, 2024)
With the continuous development of the maritime transportation indus try, many researchers paid highly attention to the research field of mar itime transportation, and numerous related studies were conducted. Therefore, it is very timely and necessary to examine the active authors, affiliations and nationalities focused on this research field, so as to enable new researchers to quickly build an understanding of this field. Based on 2,972 papers published in 66 journals from 2011 to 2020, this paper uses three indicators: number of papers, the weighted score, and the impact score, to rank top fifty authors, affiliations, and nationalities in the research f ield of maritime transportation, and show their ranking changes in five- year intervals. Finally, this paper counts the frequency of keywords from all papers and surveys the number of research topics in the past ten years from the four research fields of ‘shipping’ ‘port’ ‘maritime fleet’ and ‘green shipping’ to help researchers identify research hotspots and grasp future directions.